Neurogenin2 directs granule neuroblast production and amplification while NeuroD1 specifies neuronal fate during hippocampal neurogenesis. - Laurent Roybon; Tord Hjalt; Simon Stott; Francois Guillemot; Jia-Yi Li; Patrik Brundin (PLoS ONE)
The specification and differentiation of dentate gyrus granule neurons in the hippocampus require temporally and spatially coordinated actions of both intrinsic and extrinsic molecules. The basic helix-loop-helix transcription factor Neurogenin2 (Ngn2) and NeuroD1 are key regulators in these processes. Based on existing classification, we analyzed the molecular events occurring during hippocampal neurogenesis, primarily focusing on juvenile animals. We found that Ngn2 is transiently expressed by late type-2a amplifying progenitors. The Ngn2 progenies mature into hippocampal granule neurons. Interestingly, the loss of Ngn2 at early stages of development leads to a robust reduction in neurogenesis, but does not disturb granule neuron maturation per se. We found that the role of Ngn2 is to maintain progenitors in an undifferentiated state, allowing them to amplify prior to their maturation into granule neurons upon NeuroD1 induction. When we overexpressed Ngn2 and NeuroD1 in vivo, we found NeuroD1 to exhibit a more pronounced neuron-inductive effect, leading to granule neuron commitment, than that displayed by Ngn2. Finally, we observed that all markers expressed during the transcriptional control of hippocampal neurogenesis in rodents are also present in the human hippocampus. Taken together, we demonstrate a critical role of for Ngn2 and NeuroD1 in controlling neuronal commitment and hippocampal granule neuroblast formation, both during embryonic development and in post-natal hippocampal granule neurogenesis.